The Impact of Byond by BSI Service Disruptions on Customer Perceptions at BSI Ponorogo - Intan Nofitasari; Nur Kasanah (Journal of Economics, Law, and Humanities, 2026)
Background/Introduction: The development of information technology encourages the banking sector to provide digital services to facilitate customer transactions. One of these innovations is the Byond by BSI application. However, in its implementation, there are still service disruptions that have the potential to affect transaction activities and customer perception. Research Objectives: This study aims to analyze the impact of Byond by BSI service disruptions on customer perceptions at BSI KCP Ponorogo, identify factors that affect these perceptions, and examine the impact caused by service disruptions. Methodology: The research uses a qualitative method with a descriptive approach. Data was collected through interviews, observations, and documentation of 11 customers who use Byond by BSI at BSI KCP Ponorogo. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. Results: The results of the study show that customers' perceptions of service disruptions are diverse. Some customers feel worried and disturbed because they cannot make transactions. Factors that affect perception include application experience, transaction needs, and level of trust in banks. However, the majority of customers continue to use the service because of the convenience and efficiency offered. Unique Contribution: This research contributes to understanding the dynamics of customer perception of the disruption of Islamic banking digital services, especially in the Byond by BSI application, by highlighting the role of trust and sharia principles in maintaining customer loyalty. Conclusion: The disruption of Byond by BSI services has been proven to affect customer perceptions and transaction patterns, but does not significantly reduce interest in using digital banking services. Recommendations: Banks need to improve system stability and response to handling service interruptions, as well as strengthen communication with customers. In addition, the development of more reliable features and improving the quality of digital services based on trust and sharia principles need to be carried out.